The big book of pi : the famous number you can never know - Lehmann, Anita; Aubin, Jean-Baptiste (HELVETIQ, 2026)
"Discover what makes the number Pi so intriguing, so unknowable and so very important to our lives. For millennia, humans have been obsessed with the number Pi. We needed it for architecture, geometry and astronomy, and so it was sought by the ancient Egyptians, the Mayans and the ancient Chinese. But no one has ever found it -- and no one ever will. Meet a man who memorized ten thousand digits! How about a Pi magic trick and some Pi jokes? And check out the educator's guide at the end!"